Application Research on Telecommunication Network Cloud Computing and Virtual Desktop - Ningjun Fan (Dianxin kexue)
With the constant development of communication network，the revolution of technology，the increase of service demand and the flexible change of business，IT framework for operation and maintenance service（OMS）of telecom operators becomes more and more complex，and the OMS department is facing with such challenges as to enhance infrastructure resource utilization and sharing，relax front maintenance pressure，as well as realize quick response and promote support to business innovation. Following technological development and combining actual situation of Anhui Province，OMS department of Anhui Unicom conducted thorough research on cloud computing and virtualization technology application，and changes traditional project construction concept，so as to provide an infrastructure for maintenance management information system，realize integration of terminal desktop，and guarantee consistency，flexibility，expansibility，normalization and security of background support system based on a uniform virtualized platform.